2020
DOI: 10.1093/mnras/staa1129
|View full text |Cite
|
Sign up to set email alerts
|

The unusual broad-band X-ray spectral variability of NGC 1313 X-1 seen with XMM–Newton, Chandra, and NuSTAR

Abstract: We present results from the major coordinated X-ray observing programme on the ULX NGC 1313 X-1 performed in 2017, combining XMM–Newton, Chandra, and NuSTAR, focusing on the evolution of the broad-band (∼0.3–30.0 keV) continuum emission. Clear and unusual spectral variability is observed, but this is markedly suppressed above ∼10–15 keV, qualitatively similar to the ULX Holmberg IX X-1. We model the multi-epoch data with two-component accretion disc models designed to approximate super-Eddington accretion, all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 112 publications
6
66
0
Order By: Relevance
“…8) between the temperature of the soft component and its normalisation and therefore these relationships cannot be used reliably to support this scenario. Indeed, it has been shown that depending on the assumption of the underlying model, the correlation can disappear entirely (see e.g., Luangtip et al 2016; Walton et al 2020; see also Gonçalves & Soria 2006 for a discussion on the weaknesses of associating the soft component with an accretion disk). Nevertheless, these correlations might be useful to identify sources evolving in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8) between the temperature of the soft component and its normalisation and therefore these relationships cannot be used reliably to support this scenario. Indeed, it has been shown that depending on the assumption of the underlying model, the correlation can disappear entirely (see e.g., Luangtip et al 2016; Walton et al 2020; see also Gonçalves & Soria 2006 for a discussion on the weaknesses of associating the soft component with an accretion disk). Nevertheless, these correlations might be useful to identify sources evolving in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…luminosity, radius, temperature, etc.). As the latest studies revealed that the 0.3−10 keV band can be modelled by two thermal components (e.g., Mukherjee et al 2015;Koliopanos et al 2017Koliopanos et al , 2019Walton et al 2020), which can reproduce the curvature seen at high-energies, we first considered a phenomenological model based on two multi-colour blackbody disks (diskbb in xspec; Mitsuda et al 1984) to fit the data in this band, taking into account interstellar absorption by neutral hydrogen with two absorbing components tbabs in xspec. One was frozen at the Galactic value along the source line of sight (see Table 1), and the other one was left free to vary to take into account possible absorption from the host galaxy and the system itself.…”
Section: Choice Of Modelmentioning
confidence: 99%
See 3 more Smart Citations